来自南洋的早期华人明星 ：以姚萍为例 = An early Chinese artist from Nanyang : a case study on Yiu Ping - 张铭珈 Chong, Ming Jia (2018)
姚萍出生于南洋，以华侨的身份在上海开始演艺事业，后来活跃于香港影坛，出演了不少的粤语片，国语片和廈语片。1950 年代至 1960 年代间，姚萍从电影发展繁荣的香港回到电影才处于起步阶段的南洋。直到 1970 年代，姚萍才再次踏足香港，与邵氏签下为期三年的合约，其身影才再次出现在香港电影当中，同时也以“客串”的形式出现在电视荧幕中。本文将探讨姚萍作为华侨，在各地的局势及明星制度之下作为个体的主动性以及选择，尝试填补华语电影史上海外华人男明星被遮蔽的窘况。为了拼凑姚萍的全貌，本文阅览并收集了大量旧报刊，同时也到香港电影资料馆去观赏姚萍出演的电影《南岛相思曲》及查阅相关资料。本文将通过上述的文献，结合明星研究和华人研究，并回看当时的语境来拼凑出姚萍在上海，香港，甚至是新马地区演艺生涯的足迹。 Yiu Ping was born in Nanyang and started his acting career in Shanghai as an overseas Chinese. Later on, he went to Hong Kong and was casted in Cantonese Films, Mandarin(Guoyu) Films and Amoy Dialect Films. Between the 1950s and the 1960s, Yiu Ping moved from Hong Kong, where the film industry was relatively well developed, to Nanyang. During that time, the film industry in Nanyang was still in its infancy. Yiu Ping returned to Hong Kong again in the 1970s and signed a three-year contract with Shaw Brothers, where he then not only appeared again in Hong Kong films but also made cameo appearances in television programmes. This thesis examines Yiu Ping’s initiative and the decisions he made under the star system and the contexts of different places and times in order to refine the aspect of the research of male film stars which is often ignored. This thesis is based on materials such as newspapers, cinema magazines and the film Love Song of the South Island (available in the Hong Kong Film Archive). Star Studies and overseas Chinese Studies are applied in the analysis taking the historical context into account. Therefore, it studies Yiu Ping’s career as an artist in Shanghai, Hong Kong and Nanyang.